Cathode material for solid oxide fuel cell, cell and preparation method
By preparing powder materials with in-situ loaded alumina on LSCF, the problem of poor electrochemical stability of SOFC cathode materials is solved, and the long-term stability of battery performance and cost and environment optimization are achieved.
Patent Information
- Application Number
- CN202411633210.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-02-18
AI Technical Summary
The electrochemical stability of traditional solid oxide fuel cell (SOFC) cathode materials is poor, which affects the overall performance of the battery.
A method for preparing a cathode material for solid oxide fuel cell is adopted, including preparing LSCF powder, dispersing it in the solvent and adding aluminum nitrate and ammonium carbonate solutions, and after standing settling, drying and sintering treatment, LSCF is obtained in situ Alumina-loaded powder material.
Through this method, the electrochemical properties of the cathode material are improved, the long-term stability of the performance of solid oxide fuel cell is achieved, and the material cost is reduced and environmental pollution is reduced.
Smart Images

Figure CN119481105A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to the field of fuel cell technology, and in particular, to a method for preparing a cathode material for a solid oxide fuel cell, a cathode material for a solid oxide fuel cell, a method for preparing a solid oxide fuel cell, and a solid oxide fuel cell. Background Art
[0002] The overexploitation and use of traditional energy has caused serious environmental crises and energy shortages. In order to seek high-quality development and achieve the dual carbon goals, higher requirements have been put forward for the social structure, industrial upgrading and energy transformation. Among them, Solid Oxide Fuel Cell (SOFC), as a key device for converting chemical energy into electrical energy, has high efficiency and low environmental impact in the all-solid phase, and is crucial in the new round of energy development and utilization. As an effective energy interaction link, SOFC closely links electricity, heat and gas to build an integrated energy system. The high operating temperature of traditional SOFC (e.g., 800℃ to 1000℃) faces extremely high commercial cost challenges, such as Ni particle coarsening, reduction of the anode three-phase interface (TPB), element migration between the cathode and the electrolyte, mechanical strength degradation, cathode poisoning and its cation surface segregation, and oxidation of the interconnect device. Therefore, lowering the operating temperature has become the general trend of SOFC development.
[0003] The stability of cathode materials has a direct impact on the performance and life of SOFC. At present, cathode materials mainly include perovskite-based oxide materials. However, these materials have the problem of poor electrochemical stability, which affects the overall performance of the battery.
[0004] It should be noted that the information disclosed in the above background technology section is only used to enhance the understanding of the background of the present disclosure, and therefore may include information that does not constitute the prior art known to ordinary technicians in the field. Summary of the invention
[0005] The purpose of the present disclosure is to provide a method for preparing a cathode material for a solid oxide fuel cell, a cathode material for a solid oxide fuel cell, a method for preparing a solid oxide fuel cell, and a solid oxide fuel cell, thereby overcoming the problem of poor electrochemical performance stability of the cathode material for a solid oxide fuel cell at least to a certain extent.
[0006] According to a first aspect of the present disclosure, there is provided a method for preparing a cathode material for a solid oxide fuel cell, comprising: preparing LSCF powder; dispersing the LSCF powder in a solvent, and adding an aluminum nitrate solution and an ammonium carbonate solution, and obtaining a target mixture after mixing; allowing the target mixture to settle, and obtaining a LSCF powder preloaded with alumina after solid-liquid separation and drying the solid; and sintering the LSCF powder preloaded with alumina to obtain a powder material with alumina in situ loaded on the LSCF as a cathode material for a solid oxide fuel cell.
[0007] Optionally, preparing LSCF powder includes: dissolving lanthanum nitrate, strontium nitrate, cobalt nitrate and iron nitrate in deionized water to obtain a first solution; adding citrate to the first solution to obtain a second solution; adjusting the pH of the second solution to 8 to 10 using ammonia water to obtain a third solution; and drying, grinding and sintering the third solution to prepare LSCF powder.
[0008] Optionally, LSCF powder is dispersed in a solvent, and aluminum nitrate solution and ammonium carbonate solution are added, and after mixing, a target mixture is obtained, including: dispersing LSCF powder in a solvent, and adding aluminum nitrate solution, and after magnetic stirring, an intermediate mixture is obtained; and ammonium carbonate solution is added dropwise to the intermediate mixture to obtain a target mixture; wherein the mass ratio of LSCF powder, aluminum nitrate and ammonium carbonate is 1:(0.0005-0.05):(0.0005-0.05).
[0009] Optionally, the target mixture is allowed to settle, and after solid-liquid separation and solid drying, LSCF powder preloaded with alumina is obtained, including: allowing the target mixture to settle at room temperature for 4 to 10 hours; after removing the upper liquid of the target mixture after settling by a centrifuge, placing the solid in a drying oven at 50°C to 100°C for 6 to 12 hours to obtain LSCF powder preloaded with alumina; wherein the rotation speed of the centrifuge is 2000 rpm to 5000 rpm.
[0010] According to a second aspect of the present disclosure, there is provided a cathode material for a solid oxide fuel cell, which is prepared using the above-mentioned method for preparing a cathode material for a solid oxide fuel cell.
[0011] According to a third aspect of the present disclosure, a method for preparing a solid oxide fuel cell is provided, comprising: mixing GDC powder, a solvent, a binder and a powder material for in-situ loading of alumina on LSCF to obtain a target slurry; wherein the powder material for in-situ loading of alumina on LSCF is prepared using the above-mentioned method for preparing a cathode material for a solid oxide fuel cell; performing multiple screen printing operations on an anode electrolyte layer using the target slurry to obtain an intermediate cell; and sintering the intermediate cell to obtain a target cell.
[0012] Optionally, GDC powder, solvent, binder and powder material of in-situ alumina loading on LSCF are mixed to obtain a target slurry, including: placing GDC powder, solvent, binder and powder material of in-situ alumina loading on LSCF in a ball mill, and performing ball milling mixing to obtain the target slurry; wherein the mass ratio of the powder material of in-situ alumina loading on LSCF to GDC powder is 1:0.5 to 1:0.8; and the solid-liquid mass ratio of the target slurry is 1:0.8 to 1:1.5.
[0013] Optionally, the screen printing operation is performed 5 to 8 times; a single screen printing operation includes: using a screen printing machine to screen print once on a 200-mesh to 420-mesh screen, and drying it at 150°C to 250°C; wherein the target slurry is placed in the screen printing machine.
[0014] Optionally, the intermediate battery is sintered to obtain a target battery, including: placing the intermediate battery in a muffle furnace, and sintering at a temperature of 900° C. to 1200° C. in an air atmosphere for 3 h to 6 h to obtain the target battery.
[0015] According to a fourth aspect of the present disclosure, a solid oxide fuel cell is provided, which is prepared using any of the above-mentioned methods for preparing a solid oxide fuel cell.
[0016] In the scheme of the exemplary embodiment of the present disclosure, on the one hand, alumina is loaded in situ on the LSCF, thereby improving the stability of the electrochemical properties of the cathode material, thereby achieving the application demand of long-term stable performance of solid oxide fuel cells; on the other hand, the present disclosure can achieve precise regulation of the microstructure and performance of the material by controlling the process details; on the other hand, the loaded alumina used in the present disclosure is low-cost and environmentally friendly, and can reduce waste while ensuring material performance.
[0017] It is to be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the present disclosure. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] The accompanying drawings herein are incorporated into the specification and constitute a part of the specification, illustrate embodiments consistent with the present disclosure, and together with the specification are used to explain the principles of the present disclosure. Obviously, the accompanying drawings described below are only some embodiments of the present disclosure, and for ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without creative work.
[0019] Figure 1 A flow chart schematically shows a method for preparing a cathode material for a solid oxide fuel cell according to an exemplary embodiment of the present disclosure.
[0020] Figure 2 A flow chart schematically shows a method for preparing a solid oxide fuel cell according to an exemplary embodiment of the present disclosure.
[0021] Figure 3 A schematic diagram of a scanning electron microscope (SEM) of a powder material of in-situ loaded aluminum oxide on the LSCF of Example 1 of the present disclosure is shown.
[0022] Figure 4 The schematic diagram of the microscopic distribution of each element in the powder material of the in-situ loaded alumina on the LSCF of Example 1 of the present disclosure is shown. A represents the schematic diagram of the microscopic distribution of the lanthanum element; B represents the schematic diagram of the microscopic distribution of the strontium element; C represents the schematic diagram of the microscopic distribution of the cobalt element; D represents the schematic diagram of the microscopic distribution of the iron element; and E represents the schematic diagram of the microscopic distribution of the aluminum element.
[0023] Figure 5 A schematic diagram of X-ray diffraction (XRD) of LSCF powder before and after loading of Example 1 of the present disclosure is shown.
[0024] Figure 6 Schematic diagrams of the cathode slurry and the prepared button battery of Example 1 of the present disclosure are shown. A reflects the schematic diagram of the cathode slurry; B reflects the schematic diagram of the prepared button battery.
[0025] Figure 7 A schematic diagram showing the impedance performance test results of the battery prepared in Example 1 of the present disclosure.
[0026] Figure 8 A schematic diagram showing the test results of the electrochemical performance of the battery prepared in Example 1 of the present disclosure.
[0027] Fig. 9 A stability test chart of the battery prepared in Example 1 of the present disclosure is shown.
[0028] Fig.10A schematic diagram showing the test results of the electrochemical performance of the battery prepared in Comparative Example 1 of the present disclosure.
[0029] Fig.11 A stability test chart of the battery prepared in Comparative Example 1 of the present disclosure is shown. DETAILED DESCRIPTION
[0030] Example embodiments will now be described more fully with reference to the accompanying drawings. However, example embodiments can be implemented in a variety of forms and should not be construed as being limited to the examples set forth herein; on the contrary, these embodiments are provided so that the present disclosure will be more comprehensive and complete, and the concepts of the example embodiments are fully conveyed to those skilled in the art. The described features, structures, or characteristics may be combined in any suitable manner in one or more embodiments. In the following description, many specific details are provided to provide a full understanding of the embodiments of the present disclosure. However, those skilled in the art will appreciate that the technical solutions of the present disclosure may be practiced while omitting one or more of the specific details, or other methods, processes, steps, etc. may be adopted. In other cases, known technical solutions are not shown or described in detail to avoid obscuring various aspects of the present disclosure.
[0031] In addition, the accompanying drawings are only schematic illustrations of the present disclosure and are not necessarily drawn to scale. The same reference numerals in the figures represent the same or similar parts, and thus their repeated descriptions will be omitted. The flowcharts shown in the accompanying drawings are only exemplary illustrations and do not necessarily include all the steps. For example, some steps can also be decomposed, while some steps can be combined or partially combined, so the actual execution order may change according to actual conditions. In addition, all the terms "first", "second", "third", etc. below are only for the purpose of distinction and should not be used as limitations of the present disclosure.
[0032] La 0.6 Sr 0.4 Co 0.2 Fe 0.8 O(LSCF) has high catalytic activity and good ionic and electronic conductivity at moderate temperatures (such as less than 800°C), and can be used as a cathode material for SOFC. However, LSCF materials will have problems with electrochemical performance degradation, which are mainly caused by: Sr segregation, poisoning by Cr, S, CO and H2O, cathode failure due to mechanical damage such as cracks and delamination, and coarsening of the microstructure of the electrode. The microstructure of the porous electrode is coarsened. At the above moderate temperatures, the specific surface area (SSA) and the electrochemical reaction sites of the three-phase boundary (TPB) are reduced through the sintering / creep mechanism.
[0033] In order to alleviate the problem of microstructure coarsening, proton conductive fuel cells can be developed to reduce their operating temperature to avoid degradation caused by microstructure coarsening. This mainly relies on the innovation of new electrolytes and electrode materials for proton conductive fuel cells, and commercial applications are still far away. In addition, some SOFC products can utilize technologies based on yttria-stabilized zirconia (YSZ) or gadolinium-doped ceria (GDC) electrolytes, which can modify or redesign the materials or the microstructure of the electrode to improve performance and stability. During the sintering manufacturing process of the battery, the addition of inert second-phase ceramic nanoparticles to the electrode powder can effectively improve the morphological stability of the electrode microstructure by delaying the sintering kinetics of the electrode material.
[0034] In view of this, the present disclosure provides a new method for preparing a cathode material for a solid oxide fuel cell.
[0035] Figure 1 The flowchart of the method for preparing a cathode material for a solid oxide fuel cell according to an exemplary embodiment of the present disclosure is schematically shown. Figure 1 The method for preparing the cathode material for a solid oxide fuel cell according to the embodiment of the present disclosure comprises the following steps:
[0036] S12. Preparation of LSCF powder.
[0037] First, lanthanum nitrate, strontium nitrate, cobalt nitrate and iron nitrate can be dissolved in deionized water to obtain a first solution. Specifically, the contents of lanthanum nitrate, strontium nitrate, cobalt nitrate and iron nitrate can be determined according to the stoichiometric ratio of La element, Sr element, Co element and Fe element in LSCF.
[0038] Next, citrate can be added to the first solution to obtain a second solution. When lanthanum nitrate, strontium nitrate, cobalt nitrate and iron nitrate are understood as metal salts, the mass of the added citrate is 2 to 4 times the total mass of the above metal salts. During this process, the substance can be completely dissolved by stirring.
[0039] Subsequently, the pH of the second solution may be adjusted to 8 to 10 using aqueous ammonia to obtain a third solution.
[0040] Then, the third solution may be dried, ground, and sintered to prepare LSCF powder. Specifically, the third solution may be placed in an oven at 60° C. to 120° C. for 12 to 36 hours to form a dry gel, and then the dry gel may be ground into powder, and the powder may be placed in a muffle furnace at 1100° C. to 1300° C. and sintered for 5 to 10 hours to obtain LSCF powder.
[0041] It should be understood that the LSCF powder prepared in the present disclosure is a pure LSCF oxide phase.
[0042] S14. Dispersing LSCF powder in a solvent, adding aluminum nitrate solution and ammonium carbonate solution, and mixing to obtain a target mixture.
[0043] In an exemplary embodiment of the present disclosure, the solvent may be a dispersant such as deionized water, ethanol, etc. The solvents in the aluminum nitrate solution and the ammonium carbonate solution may be the same, for example, both are ethanol.
[0044] First, LSCF powder can be dispersed in a solvent, and aluminum nitrate solution is added for ultrasonic dispersion, and an intermediate mixture is obtained after magnetic stirring.
[0045] Next, the ammonium carbonate solution can be added dropwise to the intermediate mixture to obtain the target mixture. Specifically, the target mixture can be obtained by magnetically stirring at 50° C. to 100° C. for 6 h to 12 h, and the drop speed can be controlled at 1 drop / second to 3 drops / second. In addition, the content of the solvent required for dissolution in this process is less than or equal to 10% to 15% of the dispersed volume of the intermediate mixture.
[0046] The mass ratio of LSCF powder, aluminum nitrate and ammonium carbonate can be 1:(0.0005-0.05):(0.0005-0.05) by mass. The masses of aluminum nitrate and ammonium carbonate can be the same.
[0047] S16. The target mixture is allowed to settle, and after solid-liquid separation and solid drying, LSCF powder preloaded with alumina is obtained.
[0048] First, the target mixture can be allowed to settle at room temperature for 4 to 10 hours.
[0049] Next, a centrifuge can be used to remove the upper liquid of the target mixture after static sedimentation, and then the solid part is placed in a drying oven at 50° C. to 100° C. for 6 h to 12 h to obtain LSCF powder preloaded with alumina. The rotation speed of the centrifuge is 2000 rpm to 5000 rpm.
[0050] S18. Sintering the LSCF powder pre-loaded with alumina to obtain a powder material with alumina in-situ loaded on the LSCF as a cathode material for a solid oxide fuel cell.
[0051] According to some embodiments of the present disclosure, LSCF powder pre-loaded with alumina can be placed in a crucible and sintered at 400°C to 600°C in an air atmosphere for 3h to 6h to obtain a powder material with alumina in situ loaded on LSCF. The embodiments of the present disclosure use the powder material as a cathode material for solid oxide fuel cells.
[0052] Furthermore, the embodiments of the present disclosure also provide a cathode material for a solid oxide fuel cell, and the cathode material for a solid oxide fuel cell is prepared using the above-mentioned method for preparing the cathode material for a solid oxide fuel cell.
[0053] Furthermore, the present disclosure also provides a method for preparing a solid oxide fuel cell. Figure 2 The method for preparing a solid oxide fuel cell according to an embodiment of the present disclosure may include the following steps:
[0054] S22. Mix the GDC powder, solvent, binder and the powder material of in-situ loaded alumina on LSCF to obtain the target slurry.
[0055] In an exemplary embodiment of the present disclosure, the powder material for in-situ loading of alumina on LSCF is prepared by the above-mentioned method for preparing cathode materials for solid oxide fuel cells. 0.9 G 0.1 O 1.95 The binder is pinene alcohol containing 3wt% to 10wt% ethyl cellulose. The solvent mentioned here can be ethanol, for example.
[0056] Regarding the preparation method of the binder, first, the ethyl cellulose solid powder and pine alcohol can be mixed by ball milling. Unless otherwise specified, the ball milling mixing described in the embodiments of the present disclosure uses alumina balls with a diameter of 5 mm to 8 mm, a rotation speed of 200 r / min to 400 r / min, a time of 12 h to 24 h, and a viscosity of 2 KPa·S to 6 KPa·S.
[0057] Specifically, GDC powder, solvent, binder and powder material of in-situ loading of alumina on LSCF can be placed in a ball mill, and ball milled for 12 to 24 hours to obtain the target slurry. The speed of the ball mill can be 300 to 500 rpm, and the ball milling time can be 2 to 4 hours. The viscosity of the target slurry is 5 to 10 KPa·S.
[0058] The mass ratio of the powder material for in-situ loading of alumina on LSCF to the GDC powder can be 1:0.5 to 1:0.8; the solid-liquid mass ratio of the target slurry can be 1:0.8 to 1:1.5.
[0059] S24. Perform multiple screen printing operations on the anode electrolyte layer using the target slurry to obtain an intermediate cell.
[0060] In an exemplary embodiment of the present disclosure, the number of times the screen printing operation is performed may be, for example, 5 to 8 times. A single screen printing operation may include: screen printing once on a screen printing screen of 200 to 420 meshes using a screen printer (for example, screen printing once with a rubber soft scraper), and drying at 150° C. to 250° C.; wherein the target slurry is placed in the screen printer. During the screen printing process, the tension is controlled to be 25±2N.
[0061] Through the above treatment, the cathode thickness can be controlled to be between 10 μm and 30 μm.
[0062] S26. Sinter the intermediate battery to obtain the target battery.
[0063] Specifically, the intermediate battery can be placed in a muffle furnace and sintered at 900° C. to 1200° C. for 3 to 6 hours in an air atmosphere to obtain a target battery. During the sintering process, organic substances such as pinene alcohol and ethyl cellulose in the screen printing slurry can be completely removed, and the cathode can be sintered densely.
[0064] Furthermore, an embodiment of the present disclosure also provides a solid oxide fuel cell, which is prepared using the above-mentioned solid oxide fuel cell preparation method.
[0065] The preparation scheme of the embodiments of the present disclosure is described below by way of examples.
[0066] Example 1
[0067] First, lanthanum nitrate, strontium nitrate, cobalt nitrate and iron nitrate can be dissolved in deionized water, and citrate can be added in a ratio of 1:2 and stirred until completely dissolved. Then, a certain amount of ammonia water is used to adjust the pH to 9, and the mixture is dried in an oven at 100°C for 24 hours to form a dry gel, which is then ground into powder and sintered in a muffle furnace at 1250°C for 8 hours to form the LSCF powder described in the present disclosure.
[0068] Next, 10 g of LSCF powder and 0.74 g of aluminum nitrate nonahydrate can be ultrasonically dispersed in 200 ml of deionized water for 30 min, and then continuously magnetically stirred at 80 ° C, with the stirring speed set to 300 r / min to obtain an intermediate mixture. 1.5 g of ammonium carbonate is dissolved in 20 ml of deionized water, and after it is completely dissolved, it is added dropwise to the intermediate mixture at a speed of 2 drops / second to obtain the target mixture.
[0069] Then, the target mixture can be allowed to settle at room temperature for 6 hours, and then the upper liquid can be removed by a centrifuge at a rotation speed of 300 rpm, and the solid part can be dried in a drying oven at 90° C. for 7 hours to obtain LSCF powder preloaded with alumina.
[0070] Subsequently, the LSCF powder pre-loaded with alumina can be ground into powder using an agate mortar and then sintered in a muffle furnace. Specifically, it can be sintered at 550° C. for 6 hours in an air atmosphere to obtain a powder material with alumina in situ loaded on the LSCF.
[0071] refer to Figure 3 , the particle size of the powder material of in-situ loaded alumina on LSCF is between 300nm and 500nm, the material is uniform and the particles are small.
[0072] refer to Figure 4 , it can be clearly seen that the microscopic distribution of each element, including all elements loaded with aluminum, shows a well-uniform element distribution.
[0073] refer to Figure 5 ,In view of the low content of alumina, it can be seen from XRD that it basically maintains the main material of LSCF and has a stable structure.
[0074] Next, we will continue with Example 1 to explain the preparation scheme of the battery.
[0075] First, 8g of ethyl cellulose solid powder and 92g of pine alcohol can be weighed and mixed by ball milling, using alumina balls with a main diameter of 5mm, a rotation speed of 250r / min, and a time of 18 hours to form 8% ethyl cellulose pine alcohol with a viscosity of 3KPa·S. Then, 10g of the sintered LSCF in-situ loaded with alumina powder is mixed with 2g of GDC powder and 10g of pine alcohol binder containing 8% ethyl cellulose, and ground for 16 hours to obtain a target slurry with moderate viscosity.
[0076] Next, the target slurry was placed in a screen printing machine and screen-printed once on a 325-mesh screen with a rubber soft scraper. After drying at 180°C, this was a screen printing unit operation. This was repeated 6 times to obtain a full battery with a certain cathode thickness.
[0077] Then, the printed and dried full cell was placed in a muffle furnace and sintered at 1050°C for 4 hours in an air atmosphere to obtain a fully sintered alumina-loaded oxide cathode full cell, that is, the above-mentioned target cell.
[0078] Figure 6 A schematic diagram of the cathode slurry and the prepared button battery of Example 1 of the present disclosure is shown.
[0079] Figure 7 A schematic diagram showing the impedance performance test results of the battery prepared in Example 1 of the present disclosure. Figure 7 It can be seen that the impedance between material layers is relatively small, which proves that it has good electrochemical properties and helps to ensure good stability of battery performance.
[0080] Figure 8 A schematic diagram showing the test results of the electrochemical performance of the battery prepared in Example 1 of the present disclosure. Figure 8 It can be seen that the battery prepared based on the cathode material of the embodiment of the present disclosure has good battery output performance.
[0081] Fig. 9 The stability test diagram of the battery prepared in Example 1 of the present disclosure is shown. Fig. 9 It can be seen that the battery of Example 1 of the present disclosure can still show strong output stability in the long-term test of 100 hours.
[0082] Comparative Example 1
[0083] 10g of LSCF powder without alumina was mixed with 2g of GDC powder and 10g of pine alcohol binder containing 8% ethyl cellulose, and ground for 16 hours to obtain a target slurry with moderate viscosity. The slurry was placed in a screen printer for printing, and screen-printed once on a 325-mesh screen with a rubber soft scraper. After drying at 180°C, it was a screen printing unit operation. Repeat 6 times to obtain a full battery with a certain cathode thickness. The printed and dried full battery was placed in a muffle furnace and sintered at 1050°C for 4 hours in an air atmosphere to obtain a fully sintered oxide cathode full battery without alumina.
[0084] Fig.10 and Fig.11 The test results of the battery prepared in Comparative Example 1 are respectively characterized. Fig.10 and Figure 8 To compare and Fig.11 and Fig. 9 By comparison, it can be seen that compared with Comparative Example 1, the solution of Example 1 of the present disclosure combining the powder material of in-situ loading of alumina on LSCF has excellent output performance and long-term stability of performance.
[0085] It should be noted that although the steps of the method in the present disclosure are described in a specific order in the drawings, this does not require or imply that the steps must be performed in this specific order, or that all the steps shown must be performed to achieve the desired results. Additionally or alternatively, some steps may be omitted, multiple steps may be combined into one step, and / or one step may be decomposed into multiple steps, etc.
[0086] In addition, the above-mentioned figures are only schematic illustrations of the processes included in the method according to the exemplary embodiments of the present disclosure, and are not intended to be limiting. It is easy to understand that the processes shown in the above-mentioned figures do not indicate or limit the time sequence of these processes. In addition, it is also easy to understand that these processes can be performed synchronously or asynchronously, for example, in multiple modules.
[0087] Those skilled in the art will readily appreciate other embodiments of the present disclosure after considering the specification and practicing what is disclosed herein. This application is intended to cover any variations, uses, or adaptations of the present disclosure that follow the general principles of the present disclosure and include common knowledge or customary technical means in the art that are not disclosed in the present disclosure. The specification and embodiments are to be considered merely as exemplary, and the true scope and spirit of the present disclosure are indicated by the claims.
[0088] It should be understood that the present disclosure is not limited to the exact structures that have been described above and shown in the drawings, and that various modifications and changes may be made without departing from the scope thereof. The scope of the present disclosure is limited only by the appended claims.
Claims
1. A method for preparing a cathode material for a solid oxide fuel cell, characterized in that: include: Preparation of LSCF powder; The LSCF powder is dispersed in a solvent, and an aluminum nitrate solution and an ammonium carbonate solution are added and mixed to obtain a target mixture; The target mixture is allowed to settle, and after solid-liquid separation and solid drying, LSCF powder preloaded with alumina is obtained; The LSCF powder pre-loaded with alumina is sintered to obtain a powder material with alumina in-situ loaded on the LSCF as a cathode material for a solid oxide fuel cell.
2. The preparation method according to claim 1, characterized in that: Preparation of LSCF powder includes: dissolving lanthanum nitrate, strontium nitrate, cobalt nitrate and ferric nitrate in deionized water to obtain a first solution; adding citrate to the first solution to obtain a second solution; adjusting the pH of the second solution to 8 to 10 using aqueous ammonia to obtain a third solution; The third solution is dried, ground and sintered to prepare LSCF powder.
3. The preparation method according to claim 1, characterized in that: The LSCF powder is dispersed in a solvent, and an aluminum nitrate solution and an ammonium carbonate solution are added and mixed to obtain a target mixture, comprising: Dispersing the LSCF powder in a solvent, adding aluminum nitrate solution, and obtaining an intermediate mixture after magnetic stirring; adding an ammonium carbonate solution dropwise to the intermediate mixture to obtain a target mixture; Among them, the mass ratio of LSCF powder, aluminum nitrate and ammonium carbonate is 1: (0.0005-0.05): (0.0005-0.05).
4. The preparation method according to claim 1, characterized in that: The target mixture is allowed to settle, solid-liquid separation is performed, and the solid is dried to obtain LSCF powder preloaded with alumina, including: The target mixture was allowed to settle at room temperature for 4 to 10 hours; After removing the upper liquid of the target mixture after static sedimentation by a centrifuge, the solid is placed in a drying oven at 50° C. to 100° C. for 6 h to 12 h to obtain LSCF powder preloaded with alumina; Wherein, the rotation speed of the centrifuge is 2000rpm to 5000rpm.
5. A cathode material for a solid oxide fuel cell, characterized in that: The cathode material is prepared by the method for preparing a cathode material for a solid oxide fuel cell according to any one of claims 1 to 4.
6. A method for preparing a solid oxide fuel cell, characterized in that: include: Mixing GDC powder, solvent, binder and powder material of in-situ alumina loading on LSCF to obtain target slurry; wherein the powder material of in-situ alumina loading on LSCF is prepared by the method for preparing cathode material for solid oxide fuel cell according to any one of claims 1 to 4; performing a plurality of screen printing operations on the anode electrolyte layer using the target slurry to obtain an intermediate cell; The intermediate battery is sintered to obtain a target battery.
7. The preparation method according to claim 6, characterized in that: The GDC powder, solvent, binder and the powder material of the in-situ loaded alumina on the LSCF are mixed to obtain a target slurry, including: GDC powder, solvent, binder and powder material of in-situ loaded alumina on LSCF are placed in a ball milling tank and ball milled to obtain a target slurry; The mass ratio of the powder material of in-situ loaded alumina on the LSCF to the GDC powder is 1:0.5 to 1:0.8; and the solid-liquid mass ratio of the target slurry is 1:0.8 to 1:1.
5.
8. The preparation method according to claim 6, characterized in that: The number of times the screen printing operation is performed is 5 to 8 times; A single screen printing operation includes: The target slurry is placed in the screen printing machine, and the target slurry is printed once on a screen printing screen with a mesh size of 200 to 420. The target slurry is dried at 150° C. to 250° C.
9. The preparation method according to claim 6, characterized in that: Sintering the intermediate battery to obtain a target battery comprises: The intermediate cell was placed in a muffle furnace and sintered at a temperature of 900° C. to 1200° C. for 3 h to 6 h in an air atmosphere to obtain a target cell.
10. A solid oxide fuel cell, characterized in that: The solid oxide fuel cell is prepared by the preparation method of any one of claims 6 to 9.
Citation Information
Cited By
High-entropy cathode material, solid oxide fuel cell and preparation method
CN121044638A